LO67: The impact of CPR quality during entire resuscitation episode on survival from cardiac arrest. (15th May 2017) - Drennan, I.; Taher, A.K.; Cheskes, S.; Zhan, C.; Byers, A.; Feldman, M.; Dorian, P.; Morrison, L.J.; Lin, S.
Abstract : Introduction: High-quality cardiopulmonary resuscitation (CPR) is essential for patient survival. Typically, CPR quality is only measured during the first 10 minutes of resuscitation. There is limited research examining the quality of CPR over the entire duration of resuscitation.Objective : To examine the quality of CPR over the entire duration of resuscitation and correlate the quality of CPR to patient survival.Methods: This was a retrospective observational study using data from the Toronto RescuNET Epistry-Cardiac Arrest database. We included consecutive, adult (>18) OHCA treated by EMS between January 1, 2014 and September 30, 2015. High-quality CPR was defined, in accordance with 2015 AHA Guidelines, as a chest compression rate of 100-120/min, depth of 5.0-6.0 cm and chest compression fraction (ccf) of >0.80. We further categorized high-quality resuscitation as meeting benchmarks >80% of the time, moderate-quality between 50-80% and low-quality meeting benchmarks <50% of the resuscitation. We used multivariable logistic regression to determine association between variables of interest, including CPR quality metrics, and survival to hospital discharge.Results: A total of 5, 208 OHCA met our inclusion criteria with a survival rate of 8%. The median (IQR) duration of resuscitation was 23.0 min (15.0, 32.7). Overall CPR quality was considered high-quality for ccf in 81% of resuscitation episodes, 41% for rate, and 7% for depth. The percentage of resuscitations meeting the quality benchmarks differed between survivors and non-survivors for both depth (15% vs 6%) and ccf (61% vs 83%) (P value <0.001). After controlling for Utstein variables maintaining a chest compression depth within recommendations for >80% showed a trend towards improved survival (OR 1.68, 95% CI 0.96, 2.92). Other variables associated with survival were public location, initial CPR by EMS providers or bystanders, witnessed cardiac arrest (EMS or bystander), and initial shockable rhythm. Increasing age and longer duration of resuscitation were associated with decreased survival.Conclusion: Overall, EMS providers were not able to maintain rate or depth within guideline recommendations for the majority of the duration of resuscitation. Maintaining chest compression depth for greater than 80% of the resuscitation showed a trend towards increased survival from OHCA.